The developing family doctor system: evidence from the progress of the family doctor signing service from a longitudinal survey (2013–2016) in Pudong New Area, Shanghai - Shanshan Liu; Yan Liu; Tao Zhang; Luan Wang; Jiaoling Huang; Hong Liang; Gang Chen; Chengjun Liu; Yimin Zhang (BMC Family Practice, 2021)
Abstract Background The family doctor system is a vital part of China’s national medical and health system reform. Evidence of the degree of implementation of the family doctor system is required to assist managers and policy makers in Pudong with resource allocation planning. This study analyzed changes in indicators (family doctor team construction, contracted medical services, health management services and so on) over time to evaluate the progress of the family doctor system in Pudong. Methods We used a cross-sectional design with an online questionnaire survey to collect 3-year (2013–2016) consecutive data. The online questionnaires were completed by the doctors responsible for information reporting in each community health service center of Pudong. The data were sorted, and the indices calculated and analyzed using descriptive statistics and statistical tests. Results The proportion of registered general practitioners increased each year, from 50.8% in 2013 to 66.5% in 2016; this difference was statistically significant (P = 0.000). The number of family doctors per 10,000 permanent residents rose each year, from 1.7 in 2013 to 2.1 in 2016. The rate of contracted household residents was 55.7% in 2013 and increased to 71.7% in 2016, with the difference being significant in different years (P = 0.012). Analysis of referral services showed the people times of contracted residents transferring to higher-level hospitals from family doctors increased each year, from 172,734 in 2013 to 341,615 in 2016; differences among different regions were statistically significant for 2013–2016. The rate of health screening for contracted residents also increased each year, with statistically significant differences in different years (P = 0.000). The rate of health assessment interventions for contracted residents rose each year, with statistically significant differences in different years (P = 0.003). Conclusions The family doctor signing service in Pudong made headway in general practitioner availability, contract service rate of household residents, and providing health management services. However, problems included family doctor shortages and limited supporting policies, especially in rural and suburban areas compared with urban divisions. Increasing the enrollment rate of family doctors and speeding up the implementation of “contract service fees” are key tasks for the sustainable development of the family doctor system in Pudong.